A companion to Plato - Benson, Hugh H., 1956- (Malden, MA ; Oxford : Blackwell Pub., 2006)
Plato and Platonism remain fundamental to the practice of philosophy. This companion comprises original contributions from some of the best Platonic scholars in the world, and reflects the various ways in which they are dealing with Plato's legacy
The life of Plato of Athens / Debra Nails -- Interpreting Plato / Christopher Rowe -- The Socratic problem / William J. Prior -- Form and the Platonic dialogues / Mary Margaret McCabe -- The Socratic Elenchus / Charles M. Young -- Platonic definitions and forms / R.M. Dance -- Plato's method of dialectic / Hugh H. Benson -- Socratic ignorance / Gareth B. Matthews -- Plato on recollection / Charles Kahn -- Plato : a theory of perception or a nod to sensation? / Deborah K.W. Modrak -- Knowledge and the forms in Plato / Michael Ferejohn -- The forms and the sciences in Socrates and Plato / Terry Penner -- Problems for forms / Mary Louise Gill -- The role of cosmology in Plato's philosophy / Cynthia Freeland -- Plato on language / David Sedley -- Plato and mathematics / Michael J. White -- Platonic religion / Mark L. McPherran -- The Socratic paradoxes / Thomas C. Brickhouse and Nicholas D. Smith -- The Platonic soul / Fred D. Miller, Jr. -- Plato on eros and friendship / C.D.C. Reeve -- Plato on pleasure as the human good / Gerasimos Santas -- The unity of the virtues / Daniel Devereux -- Plato on justice / David Keyt -- Plato's concept of goodness / Nicholas White -- Plato on the law / Susan Suavé Meyer -- Plato and the arts / Christopher Janaway -- Learning about Plato from Aristotle / Christopher Shields -- Plato and Hellenistic philosophy / A.A. Long -- Plato's influence on Jewish, Christian, and Islamic philosophy / Sara Ahbel-Rappe
Includes bibliographical references and index
Keywords: Plato